2006
DOI: 10.1007/s11095-005-8717-3
|View full text |Cite
|
Sign up to set email alerts
|

Varying the Unsaturation in N4,N9-Dioctadecanoyl Spermines: Nonviral Lipopolyamine Vectors for More Efficient Plasmid DNA Formulation

Abstract: The dienoic fatty acyl spermine conjugate N4,N9-dilinoleoyl spermine efficiently condenses DNA and achieves the highest transfection levels among the studied lipopolyamines in cultured cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
66
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
5
2

Relationship

4
3

Authors

Journals

citations
Cited by 33 publications
(69 citation statements)
references
References 60 publications
3
66
0
Order By: Relevance
“…NH 3 200:10:1 to 100:10:1 to 50:10:1; v/v/v). N 4 ,N 9 -Dioleoyl-1,12-diamino-4,9-diazadodecane 1 Prepared via N 1 ,N 12 -ditrifluoroacetyl-N 4 ,N 9 -dioleoyl-1,12-diamino-4,9-diazadodecane (36), the target lipopolyamine displayed HRMS: found (m/z [M+H] + ) 731.7115, C 46 H 91 N 4 O 2 requires 731.7142 (Δ ppm 3.7), consistent with the data previously reported (2,3).…”
Section: General Detailssupporting
confidence: 88%
See 2 more Smart Citations
“…NH 3 200:10:1 to 100:10:1 to 50:10:1; v/v/v). N 4 ,N 9 -Dioleoyl-1,12-diamino-4,9-diazadodecane 1 Prepared via N 1 ,N 12 -ditrifluoroacetyl-N 4 ,N 9 -dioleoyl-1,12-diamino-4,9-diazadodecane (36), the target lipopolyamine displayed HRMS: found (m/z [M+H] + ) 731.7115, C 46 H 91 N 4 O 2 requires 731.7142 (Δ ppm 3.7), consistent with the data previously reported (2,3).…”
Section: General Detailssupporting
confidence: 88%
“…Our NVGT focus is on lipopolyamines composed of two long-carbon chains (or a steroid) covalently bound to a polyamine e.g. spermine (1,12-diamino-4,9-diazadodecane) (2,3). Other research groups are investigating a variety of alternative approaches, including: naked polynucleotides, gene gun (bound to gold particles), electroporation, and the use of a wide variety of cationic lipids (lipoplexes) (4)(5)(6)(7)(8) and cationic polymers (polyplexes), for reviews see: (9)(10)(11)(12).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Different saturation levels are shown to influence DNA formulation. 21 Comparing all the unsaturated derivatives, DNA retardation is observed at lower concentrations with complexes formulated with linolylspermine. The DNase I protection assay, on the other hand, is not very conclusive, as bands do not seem to follow any trend.…”
Section: Resultsmentioning
confidence: 99%
“…Polyamines have been extensively used for the development of nonviral vectors and this includes studies in which lipospermines typically either contain double or have longer hydrocarbon chains. 18,21,[28][29][30][31] It has previously been suggested that DNA-binding affinity is a function of both charge and hydrophobicity. 19,32 However, to what degree this affinity is beneficial for gene delivery is not clear.…”
Section: Discussionmentioning
confidence: 99%